Energy absorption capability of carbon nanotubes dispersed in resins under compressive high strain rate loading. (April 2015) - Pandya, K.S.; Naik, N.K.
Abstract: The focus of the present study is on energy absorption capability ( EA ) of carbon nanotubes (CNTs) dispersed in thermoset epoxy resin under compressive high strain rate loading. Toward this objective, high strain rate compressive behavior of multi-walled carbon nanotube (MWCNT) dispersed epoxy is investigated using a split Hopkinson pressure bar. The amount of MWCNT dispersion is varied up to 3% by weight. Calculation methodology for the evaluation of EA of individual CNTs and CNTs dispersed in resins/composites is presented. Quantitative data on EA of individual CNTs and CNTs dispersed in resins under quasi-static and high strain rate loading is given.